PpNUDX8, a Peach NUDIX Hydrolase, Plays a Negative Regulator in Response to Drought Stress - He, HuaJie; Zhang, YuZheng; Wen, BinBin; Meng, XiangGuang; Wang, Ning; Sun, MingYun; Zhang, Rui; Zhao, XueHui; Tan, QiuPing; Xiao, Wei; Li, DongMei; Fu, XiLing; et al. (Frontiers in Plant Science, 2022)
Drought stress is a serious abiotic stress source that affects the growth and fruit quality of peach trees. However, the molecular mechanism of the NUDIX hydrolase family in peaches in response to drought stress is still unclear. Here, we isolated and identified the PpNUDX8 (Prupe.5G062300.1) gene from the peach NUDIX hydrolase family, and found that PpNUDX8 has a typical NUDIX hydrolase domain. In this study, we performed 15% PEG6000 drought treatment on peach seedlings, and qRT–PCR analysis showed that 15% PEG6000 induced the transcription level of PpNUDX8. Overexpression of PpNUDX8 reduced the tolerance of calli to 4% PEG6000 treatment. Compared with wild-type apple calli, PpNUDX8 transgenic apple calli had a lower fresh weight and higher MDA content. After 15% PEG6000 drought treatment, PpNUDX8 transgenic tobacco had a greater degree of wilting and shorter primary roots than Under control conditions. The chlorophyll, soluble protein, and proline contents in the transgenic tobacco decreased, and the MDA content and relative conductivity increased. At the same time, PpNUDX8 negatively regulated ABA signal transduction and reduced the transcriptional expression of stress response genes. In addition, PpNUDX8 was not sensitive to ABA, overexpression of PpNUDX8 reduced the expression of the ABA synthesis-related gene NCED6 and increases the expression of the ABA decomposition-related gene CYP1 in tobacco, which in turn leads to a decrease in the ABA content in tobacco. In addition, Under control conditions, overexpression of PpNUDX8 destroyed the homeostasis of NAD and reduced nicotinamide adenine dinucleotide (NADH) in tobacco. After 15% PEG6000 drought treatment, the changes in NAD and NADH in PpNUDX8 transgenic tobacco were more severe than those in WT tobacco. In addition, PpNUDX8 also interacted with PpSnRk1γ (Prupe.6G323700.1).